Views Of School Managers, Parent-Teacher Association Board Members And Parents On Why Parent-Teacher Associations Fail To Raise Donations - Gokyer, Necmi; Alpinanc, Mehmet (Elsevier Science Bv, 2014)
This study aims to identify the reasons why parent-teacher associations are not able raise donations according to the views of school managers, parent-teacher association board members and parents. The financing of kindergartens, primary schools and secondary schools occur through parent-teacher associations. It is a well-known fact that as the sources listed by item 15 in the Parent-Teacher Association Regulation are not enough to meet the needs of schools, they try to raise donations and this creates many problems. This study intends to reveal these problems. The population of the study comprises 6,078 parents and 63 managers and parent-teacher association board members from 7 schools selected from among the school located in central Elazig by considering the socioeconomic level of parents and the cultural environment of the schools. The sample included 833 parents and the above number of school managers and parent-teacher association board members who were selected randomly. The study used questionnaires to collect data. (C) 2014 Published by Elsevier Ltd.
4th World Conference on Learning, Teaching and Educational Leadership (WCLTA) -- OCT 27-29, 2013 -- Univ Barcelona, Barcelona, SPAIN
Keywords: Parent-teacher association; donations; parents; board members